THE EFFECT OF PICTURE AND PICTURE MODEL TO THE STUDENTS SKILL ON WRITING BIOGRAPHY - M.Pd, kamisah S.Pd (JURNAL EDUCATION AND DEVELOPMENT, 2018)
The purposes of this research to find out whether there was a significant effect of picture and picture model to the students skill on writing biography. This research conducted by using experimental method one group pretest-posttest design. The populations of this research the entire tenth grade students consist of 178 students. Sample taken by cluster sampling technique, technique for collecting data were observation sheet and giving essay test, the total sample 38 students. After calculating the data, it was found the mean score of students writing biography before using picture and picture model 32.47, it was categorized âFailâ, while the mean score of students writing biography after using picture and picture model 75.97, it categorized âGoodâ. The alternative hypothesis accepted. Where the result of hypothesis test shows that ttest was 36.46. The degree of freedom (df) was N- 1 =38-1 = 37. The score df of ttable at 5% significant level from 37 was 2.02. Based on calculation ttest was higher than ttable (ttest > ttable = 36.46 > 2.02). It can be concluded that thereâs a significant effect of Picture and Picture Model to the studentsâ skill on writing biography at the tenth grade of SMA Negeri 1 Tukka.